2019
DOI: 10.1002/jsfa.9606
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rosemary (Rosmarinus officinalis L.) extracts and dry ice on the physicochemical stability of omega‐3 fatty‐acid‐fortified surimi‐like meat products

Abstract: BACKGROUND Lipid peroxidation entails major quality degradation in omega‐3 (ω‐3) fatty‐acid‐fortified surimi‐like meat products upon storage. Currently, the use of label‐friendly alternatives to synthetic antioxidants is encouraged in the industry. Hence, we aimed to examine the applicability of the hurdle‐technology concept, using an 80% (v/v) ethanol solution to obtain rosemary extracts (REs) containing substantial amounts of polyphenol, and dry ice (DI) which can create a cryogenic environment, on the physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 33 publications
0
8
0
1
Order By: Relevance
“…In this regard, several authors reported the promising use of rosemary (Rosmarinus officinalis L.) extract to extend the shelf life of meat products. Wang et al [92] evaluated the physicochemical stability of omega-3 fatty-acid-fortified surimi-like meat products with ethanolic extracts of rosemary. The authors observed that their addition during the chopping procedure would prolong the shelf life of these type of products in the industry, decreasing lipid oxidation markers such as POV, CDs, and TBARs.…”
Section: Plant Extracts Obtained By Emerging Technologiesmentioning
confidence: 99%
“…In this regard, several authors reported the promising use of rosemary (Rosmarinus officinalis L.) extract to extend the shelf life of meat products. Wang et al [92] evaluated the physicochemical stability of omega-3 fatty-acid-fortified surimi-like meat products with ethanolic extracts of rosemary. The authors observed that their addition during the chopping procedure would prolong the shelf life of these type of products in the industry, decreasing lipid oxidation markers such as POV, CDs, and TBARs.…”
Section: Plant Extracts Obtained By Emerging Technologiesmentioning
confidence: 99%
“… Kim and Park (2008) indicated that salt addition is required to extract myofibrillar proteins and obtain the desired texture upon cooking in the surimi gelation. Almost all surimi seafood was manufactured with salt up to 2.5% to maintain taste, texture, and microbial safety ( Kim and Park, 2008 ; Wang et al., 2016 ; Wang et al., 2019 ). The measurement of centrifugation loss is developed to assess a fast determination of WHC in meat products, and purge loss is to understand a loss from meat products influenced by the myofibrils’ capacity that holds water in the meat products ( Kristensen and Purslow, 2001 ).…”
Section: Resultsmentioning
confidence: 99%
“…As we know, chicken meat has many desirable nutritional characteristics, such as low lipid content and a relatively high concentration of polyunsaturated fatty acids that can be further increased by specific dietary strategies. Recently, our team invested that CS batters extracted from spent hen breast can be fortified with flaxseed oil to increase its nutritional value ( Wang et al., 2016 ), and the shelf-life of this flaxseed-oil fortified chicken surimi can be extended by adding a rosemary extract and dry ice in the manufacturing procedure ( Wang et al., 2019 ). Moreover, our recent report indicated that this surimi product's flaxseed-oil addition and texture could be enhanced and improved by wheat fiber addition (dietary fiber), respectively ( Wu et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The lipid extraction from digesta samples and methylation of free fatty acids were conducted according to previous studies . The fatty acid methyl esters were separated and quantified with a Agilent 7890B GC system equipped with a flame ionization detector and an HP‐88 capillary column (100 m, 0.25 mm id, 0.2 μm; Agilent Technologies Inc., Santa Clara, CA, USA).…”
Section: Methodsmentioning
confidence: 99%